Of cattle and feasts: Multi-isotope investigation of animal husbandry and communal feasting at Neolithic Makriyalos, northern Greece. - Petra Vaiglova; Paul Halstead; Maria Pappa; Sevi Triantaphyllou; Soultana M Valamoti; Jane Evans; Rebecca Fraser; Panagiotis Karkanas; Andrea Kay; Julia Lee-Thorp; Amy Bogaard (PLoS ONE)
The aim of this study is to investigate livestock husbandry and its relationship to the mobilization of domestic animals for slaughter at large communal feasting events, in Late Neolithic Makriyalos, northern Greece. A multi-isotope approach is built that integrates analysis of: δ13C and δ15N values of human and animal bone collagen for understanding long-term dietary behavior,Incremental δ13C and δ18O values of domestic animal tooth enamel carbonate for assessing seasonal patterns in grazing habits and mobility, and87Sr/86Sr ratios of cattle tooth enamel for examining the possibility that some of the animals consumed at the site were born outside the local environment. The findings indicate that cattle had isotopically more variable diets than sheep, which may reflect grazing over a wider catchment area in the local landscape. Cattle products did not make a significant contribution to the long-term dietary protein intake of the humans, which may indicate that they were primarily consumed during episodic feasting events. There is no indication that pasturing of livestock was pre-determined by their eventual context of slaughter (i.e. large-scale feasting vs. more routine consumption events). Two non-local cattle identified among those deposited in a feasting context may have been brought to the site as contributions to these feasts. The evidence presented provides a more detailed insight into local land use and into the role of livestock and feasting in forging social relationships within the regional human population.